Perancangan Multi Node Web Server Menggunakan Docker Swarm dengan Metode Highavability - Ahmad Rivaldi; Ucuk Darusalam; Deny Hidayatullah (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Container-based virtualization is very popular among programming development in a lightweight virtualization because where the Linux kernel can divide resource-using containers to prevent uninterrupted performance between And as a burden divider in tackling the many incoming bandwidth. One of the most commonly used container-based virtualization is Docker. Docker itself is an open source software that can be changed to your liking. Docker containers can be used for clustering Web servers. It aims to reduce "a single point of failure" (SPOF) in a Web server. However, arranging a lot of containers is very complicated, but Docker has an engine to set it up called Docker Swarm.  With it in the NGINX management help so that it can cause the resource between hosts is not divided on average. Therefore the research aims to distribute Web server traffic across the host with loadbalancing based on time-based monitoring and failover resources. By winning the low resources or resources used by Docker in the operation of an application that can be virtualized only what is needed